A Systematic Review and Meta-analysis of Clinical Trials of Neuraxial, Intravenous, and Inhalational Anesthesia for External Cephalic Version. Issue 3 (25th September 2021) - Hao, Q.; Hu, Y.; Zhang, L.; Ross, J.; Robishaw, S.; Noble, C.; Wu, X.; Zhang, X.
Abstract : ( Anesth Analg . 2020;131:1800–1811) External cephalic version (ECV) is a procedure used on parturient women at term during vaginal delivery of noncephalic fetal presentation. Data suggests that successful ECV at term decreases the rate of cesarean delivery and overall financial cost without increasing neonatal complications. While several interventions have been shown to increase the efficacy of ECV, there is no consensus regarding anesthetic care in association to ECV. This study aims to analyze data to compare maternal and fetal outcomes of ECV techniques (with and without inhalational, neuraxial, and intravenous anesthesia) and the association with cesarean delivery rates.